DAKWAH MELALUI PENDIDIKAN ISLAM : TANTANGAN MENDIDIK KARAKTER MUSLIM MILENIAL - Ahmad Noviansah (MADDINA: Jurnal Manajemen Dakwah, 2024)
This research is intended to find out the challenges that exist in da'wah through Islamic education in the millennial generation. In Muslim society, the word da'wah, both as a concept and activity, is often identified as education (tarbiyah) for the reason that in da'wah there is an element of education and in education there is an element of da'wah, moreover both activities do not know age. This millennial era is defined by some experts as the era of back to spiritual and moral or back to religion. It is a time of return to spiritual, moral and religious teachings. The challenge of today's millennial generation is how to turn the information obtained by someone into meaningful knowledge. The main assets of the millennial generation in this era are ideas and creativity, research and findings supported by science. Millennial generation is a generational terminology that is currently widely discussed by many people in the world in various fields. Millenials or also known as Millennials or Generation Y is a demographic group (cohort) after Generation X. Social researchers often group the generation born between the 1980s and 2000s as millennials. It can be said that the millennial generation is today's young generation who are currently aged in the age range of 21 to 41 years. This research is intended to find out the challenges that exist in da'wah through Islamic education in the millennial generation. In Muslim society, the word da'wah, both as a concept and activity, is often identified as education (tarbiyah) for the reason that in da'wah there is an element of education and in education there is an element of da'wah, moreover both activities do not know age. This millennial era is defined by some experts as the era of back to spiritual and moral or back to religion. It is a time of return to spiritual, moral and religious teachings. The challenge of today's millennial generation is how to turn the information obtained by someone into meaningful knowledge. The main assets of the millennial generation in this era are ideas and creativity, research and findings supported by science. Millennial generation is a generational terminology that is currently widely discussed by many people in the world in various fields. Millenials or also known as Millennials or Generation Y is a demographic group (cohort) after Generation X. Social researchers often group the generation born between the 1980s and 2000s as millennials. It can be said that the millennial generation is today's young generation who are currently aged in the age range of 21 to 41 years.